Credit Growth and Bank Soundness : Fast and Furious? - Igan, Deniz; Pinheiro, Marcelo (Washington, D.C. : International Monetary Fund, 2011)
We examine the risks to bank soundness associated with credit booms in a large set of countries. Using bank-level data in 90 countries between 1995 and 2005, we analyze the relationship between credit growth and bank soundness taking into account the potential two-way causality. We find that, while sounder banks tend to grow faster at moderate-growth periods, credit growth becomes less dependent on soundness during booms. These findings shed some light on why credit booms are often associated with financial crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet